The Effect of Reciprocal Teaching on Reading Comprehension Skill of the Eleventh Grade Students of MAN 3 KANDANGAN KEDIRI - Novi Rina Dewi; ali muchasan (INOVATIF: Jurnal Penelitian Pendidikan, Agama, dan Kebudayaan, 2018)
This study is aimed to know the effectiveness of Reciprocal Teaching on Reading Comprehension Skill at Eleventh Students of MAN 3 Kandangan. The research discused about Reciprocal Teaching compared with Conventionsal Method. Here the researcher hypothesized that the Eleventh grade students of MAN 3 Kandangan taught using Reciprocal Teaching have higher score in reading comprehension than those are taught using Conventional Method. Before determining the students into the groups, it was done homogeneous test to know wether the two groups had approximately the same level of reading proficiency. Afterword, the groups were assigneed to the experimental group and control group by conducting lottery. To collect the data the researcher tested the two groups by giving multiple choices test at different time. The data were obtained from the score of posttest in each group. The data in this research were analyzed using the Independent Sample t-test and computed by using SPSS program with significant level of 5%. The result revealed that the statistical computation value of the observed t(to) was higher than t-table (4.389>2.045). Therefore, the null hypothesis was rejected, while the alternative hypothesis was accepted. It can be conclude that Elevents students of MAN 3 Kandangan taught by using Reciprocal Teaching have better reading comprehension skill than those taught by using Conventional Method.